Trading time for space: a new approach to investigate the EEG neural mechanisms of fine motor brain based on ICA-optimized traceability network analysis - Anmin Gong; Huijie Man; Xinyu Shi; Sinan Li; Xiuyan Hu; Bowen Gong; Ting Shi; Yunfa Fu (Cognitive Neurodynamics, 2026)

Recent progress on biological control of Fusarium wilt in vegetable crops - Feng Xiong; Mingfeng Guo; Yawen Liu; Xiaochen Liu; Jiahui Fu; JunZhu Gao; Man Yang; Rui Ma; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Crop Protection, 2026)

Robust identification of known and unknown weeds with crop center localization based on Open-set object detection - Lamin L. Janneh; Leilei He; Bryan Gilbert Murengam; Xiaojuan Liu; Mbemba Hydara; Man Xia; Rui Li; Yanxin Zhang; Longsheng Fu (Precision Agriculture, 2026)

Nanomaterials as plant delivery carriers: transport mechanisms and design principles - Ye Li; Yezhuo Zhang; Zhun Zhang; Xi Zhang; Hongyang Wu; Man Zhang; Zhuo Li; Yinglang Wan; Yujie Fu; Wei Dong; Ruili Li; Jinxing Lin (Science China Life Sciences, 2026)

Retraction notice to “Perfluorinated compound correlation between human serum and drinking water: Is drinking water a significant contributor?” [Sci. Total Environ. 873 (2023) 162471] - Shengnian Wu; Tingting Yuan; Wei Fu; Huiyu Dong; Ying Zhang; Man Zhang; Caifang Jiang; Qian Xu; Liping Zhang; Zhimin Qiang (Science of The Total Environment, 2026)

Preparation and characterisation of two new malonylated rare ginsenosides by acid hydrolysis and their anti-hepatoma activities - Ya-Qian Lu; Xiao-Man Jin; Fu-Rui Zhang; Mei-Hui Li; Wen-Wen Li; Wei Li; Chun-Su Yuan; Zhi Liu (Natural Product Research, 2026)

Acetic Acid Suppresses Perennial Ryegrass Growth In Vitro by Disrupting Gibberellin and Auxin Homeostasis and Restricting Cell Expansion - Hao Guan; Caiyi Xie; Weiyu Jia; Ruiting Ouyang; Yuhan Xia; Yuhan Fu; Yi Man; Huaiyang Hou; Yingjun Chi; Bin Xu; Jing Zhang (Journal of Plant Growth Regulation, 2026)

Genesis of the Zhamuqin Pb−Zn−Ag polymetallic deposit in the middle-southern Great Xing’an Range, NE China: constraints from H−O−S−Pb isotope geochemistry and geochronology - Peng He; Man Li; Shuo Guo; Fei Teng; Xianyu Cheng; Qilong Fu (International Geology Review, 2026)

Synergistic effect of high-voltage alternating and static electric fields on quality maintenance of partially frozen Litopenaeus vannamei via stabilization of protein structure - Zekai Fan; Chen Li; Bing Chen; Ning Wang; Man Fu; Donglei Luan; Zunying Liu; Kaining Han; Shiyuan Dong (Food Chemistry, 2026)

λ-Carrageenan inhibits African swine fever virus infection potentially through its interaction with the viral envelope protein CD2v - Kun Han; Limeng Sun; Can Jin; Siqi Wan; Caiqin Cao; Yulu Yue; Man Lu; Xiaotong Wang; Yi Zheng; Hailong Liu; Yilin Guo; Dagang Tao; et al. (Carbohydrate Polymers, 2026)

Contrasting responses of bacterial-mediated soil organic phosphorus transformations to varying rates of nitrogen addition in a Cunninghamia lanceolata plantation - Xiang Zhang; Qiong Zhao; Li-Man Wei; Lin-Hui Wu; Xiang-Min Fang; Yong-Hong Ma; Fu-Sheng Chen (Applied Soil Ecology, 2026)

C-Cu/Zn/Al bonding carbon-based composites by DEHP-rich PVC/spent copper catalyst dechlorination co-processing for chemiluminescence detection of polystyrene microplastics - Yingying Qi; Man Zhao; Fu-Rong Xiu; Wenxia Jing; Wei Yang (Journal of Hazardous Materials, 2026)

A win–win strategy for balancing yield and CO2 emissions via shifts from r- to K-strategists in a mulched bamboo plantation - Tingting Cao; Quan Li; Meng Lei; Jiahui Zeng; Jiarui Fu; Simin Wang; Man Shi; Zhikang Wang; Xinzhang Song (Applied Soil Ecology, 2026)

Application of Magnetic-Seismic Geophysical Prospecting Technology in Identifying the Carboniferous Volcanic Rocks in the Chepaizi, West Margin of Junggar Basin - Guo-hua Jiao; Wei-ping Zhang; Jin-ke Zhou; Fu-gang Sun; Hai-tao Yang; Man Li; Zhu-qiang Li (Applied Geophysics, 2026)

Hybrid crested porcupine optimizer decomposition method and deep neural network to predict long-term rainfall - Man-Hong Fan; Xiao-Ying Ma; Shi-Qi Xu; Rui-Lin Fu (Theoretical and Applied Climatology, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

PRRSV nucleocapsid and nonstructural proteins dual-regulate CD40 expression via ATF-2 and AP-1 pathways - Chaolun Fu; Hongyan Gao; Yingchao Li; Chang Liu; Yuzhong Zhao; Youbo Li; Zhong Liu; Man Lu; Yang Shen; Yajing Xing; Yu Wang; Xiaotong Wu; et al. (Veterinary Microbiology, 2026)

Multi-Feature and Multi-Step Monthly Rainfall Forecasting with the Hybrid VMD-LSTM-CATNet Model in Diverse Climatic Regions - Man-Hong Fan; Xiao-Ying Ma; Shi-Qi Xu; Rui-Lin Fu; Zhong-Xing Tao (Water Resources Management, 2026)

Multi-media distribution, partitioning, and risks of tire additives and their transformation products in coastal waters of China - Chao Liu; Shuang Lu; Min Lv; Longwen Fu; Mingsan Man; Yize Du; Jing Ding; Wei Liu; Lingxin Chen (Marine Pollution Bulletin, 2026)

Petrology, geochemistry and geochronology of the Kekeya ash (SW Tarim Basin): Implications for its origin and provenance - Jia-Jun Mo; Yu-Ting Zhong; Man Wang; Le Zhang; Qiong Wu; Qiang Ma; He Wang; Jahandar Ramezani; Xiao-Long Huang; Fu-Yuan Wu; Yi-Gang Xu (Lithos, 2026)

Engineered hydrogels for siRNA delivery: From smart design to therapeutic impact - Shaohui Geng; Yijin Jiang; Huawei Wang; Anqi Liu; Xiuwen Wang; Ran Man; Jingyuan Fu; Yiwei Guan; Zi Ye; Zixuan Shu; Han Sheng; Jinian Wei; et al. (Chemical Engineering Journal, 2026)

Construction and temporal external validation of interpretable machine-learning models for predicting tigecycline-associated hypofibrinogenemia - An Fu; Daihong Guo; Man Zhu; Le Cai; Ao Gao; Liqiang Cui (European Journal of Clinical Pharmacology, 2026)

Tassel counting of individual ridge from UAV RGB imagery based on YOLOv8m with deep SORT and double-step Otsu thresholding algorithm by filtering abnormal IDs for maize breeding - Man Xia; Leilei He; Yu Gu; Xiaojuan Liu; Bryan Gilbert Murengami; Lamin L. Janneh; Rui Li; Yan Long; Anastasia Grecheneva; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Low carbon chemiluminescence detection of glucose by boosting of CCu bonding nanocomposites from epoxy resin waste debromination treatment - Yingying Qi; Man Zhao; Fu-Rong Xiu; Li Bai; Xiang Gao (Food Chemistry, 2025)

Targeted screening of pancreatic lipase inhibitory peptides from quinoa protein hydrolysates by ligand fishing - Zeyue Fu; Junhao Wang; Chunxiao Wu; Jinfan Qin; Byung-Hoo Lee; Man Li; Qingjie Sun; Wenting Tang (Food Chemistry, 2025)

Thymus serpyllum extract exerts anticancer activities against colorectal cancer by modulating metastasis, cell cycle arrest, and apoptosis - Chao-Yuan Yao; Kai-Fu Chang; Ju-Huei Chien; Xiao-Fan Huang; Yu-Chi Chen; Ming-Chang Hsieh; Nu-Man Tsai (Molecular Biology Reports, 2025)

3D Geomechanical Modeling for Sweet Spot Identification in Thin-Layer Carbonate Reservoirs - Jian Yang; Zhouyang Wang; Miao Yang; Yuanyu Yang; Xucheng Li; Le Luo; Yan Fu; Man Huang; Zhi Zhong; Dongchao Su; Zikun Li; Fulong Ning (Geotechnical and Geological Engineering, 2025)

Selective kernel convolution with global attention mechanism for multitask change detection in optical and SAR images - Tonggen Yang; Liang Huang; Bo-Hui Tang; Zhitao Fu; Zhen Zhang; Zhongxi Ge; Man Zhang; Siming Pu (Earth Science Informatics, 2025)

Insights into the multi-media spatiotemporal distribution, partitioning, and risks of pharmaceuticals and personal care products in the southern Bohai Sea - Shuang Lu; Han Chen; Min Lv; Peng Zhang; Longwen Fu; Mingsan Man; Wei Zhang; Dongliang Wang; Jing Ding; Wei Liu; Lingxin Chen (Journal of Environmental Management, 2025)

Antibiotic resistance genes in multi-matrices of Chaohu Lake: Spatiotemporal variation and correlation with pesticides and PPCPs - Hao Yang; Hongwei Fu; Yutong Zhao; Run Li; Man Cao; Yi Liu; Yachao Ni; Wei Song; Yangyang Liang; Panyuan Cai; Wei Chang; Fangbiao Tao; et al. (Journal of Hazardous Materials, 2025)

Simulation of the enhancement of mass transfer on removal behavior of CH3I in microchannel reactor - Qing He; Lei Zhang; Man Fu; Guorui Zhu (Journal of Environmental Chemical Engineering, 2025)

Macrophage and keratinocyte cell assays suggest that the supercritical CO2 extract of black soybean possesses anti-inflammatory and skin barrier-protective effects - Ying Wu; Jia-Ying Wu; Jing-Xuan Bai; Xiao-Qi Wang; Amy Sze-Man Li; Xiao-Yun Fan; Rui-Xuan Han; Li Wang; Xiaobing Dou; Xiu-Qiong Fu; Zhi-Ling Yu (Food Research International, 2025)

Analgesic Effects of Acupressure on Jing-jiaji Acupoints in a Rat Model of Cervical Spondylotic Radiculopathy - Shang-Hong Jiang; Song Yang; Ling Meng; Ling-Yao Xie; Jia-Ni Yang; Si-Qi Li; Ke-Ying Liao; Zhi-Fang Qiu; Yao-Yao Xiao; Man-Di Fu; Zhi-Li Liu; Xue-Yu Jiang (Molecular Neurobiology, 2025)

Synergistic effects of PGPR and organic fertilizer on soil fertility, enzyme activities, and microbial community composition in saline-alkali rice systems - Mingfeng Guo; Junzhu Gao; Man Yang; Yawen Liu; Jiahui Fu; Rui Ma; Feng Xiong; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Applied Soil Ecology, 2025)

Temporal lag in nitrogen use efficiency and its implications for sustainable cropland management - Jincheng Li; Jiaxing Fu; Taher Kahil; Dor Fridman; Kaikui Cai; Shasha Xu; Gang Zhao; Man Zhang; Xingxing Duan; Yue Qin; Yong Liu (Resources, Conservation and Recycling, 2025)

Evolution and innovation of the metazoan burrowing behaviour from Ediacaran-Cambrian transition, eastern Yunnan - Da Li; Man Li; Yongan Qi; Guochun Zhao; Jian Fu; Fuqiang Guo; Chengjun Zhang; Jianyu Guan; Shishan Zhang (Precambrian Research, 2025)

Alveolar surfactant-mimicking inhaled biomimetic nanovaccine with alveolar macrophage-targeting property potentiates anti-mpox immunity - Bin Li; Jiamei Wang; Judun Zheng; Wei Wang; Lingjie He; Yan Yan; Xinting Fu; Xingjie You; Man Gu; Han Duan; Yue Jia; Qin Gu; et al. (Chemical Engineering Journal, 2025)

Highly efficient and convenient QuEChERS using ZIF-67 derived magnetic nanoporous carbon for determination of carbamate pesticides in various vegetable and fruit samples - Zi-Ling Li; Xiao-Run Qi; Yi-Heng Xu; Jia-Qi Zhao; Gui-Fu Zuo; Man-Man Wang (Food Chemistry, 2025)

Highly effective adsorption, porous and charged CAP@Ui0-66-NH2@PPy hybrid fibrous membrane based on MOFs for Cr (VI) removal from wastewater - Tiantian Li; Zhining Huang; Mengfan Hu; Yuen Hu; Ke Quan; Man Zhou; Yao chen; Shaoju Fu (Chemical Engineering Journal, 2025)

Evaluating overhanging slope failure mechanisms and rockfall trajectories through integrated UAV imagery and discrete element modeling - Meng-Chia Weng; Geng-Man Zhang; Yu-Yao Fu; Hoang-Khanh Le; Yu-Hui Kao (Landslides, 2025)
To evaluate the threat of rockfall from an overhanging slope above a bridge, this study proposes a comprehensive analysis procedure to assess the failure mechanisms of the slope and the associated rockfall trajectories. The analysis utilizes high-resolution point cloud data obtained through integrated UAV-based imagery technology, enabling a detailed evaluation of joint configurations and slope stability. The geometric reconstruction of unstable rock blocks, combined with stereographic projections, provides an in-depth analysis of potential failure modes. Discrete element modeling (DEM) is employed to simulate the failure processes and predict rockfall trajectories, with particular emphasis on the potential risks to the underlying bridge. The results indicate that rockfall events near the bridge are primarily driven by wedge-shaped failures, a finding confirmed by both the proposed inverted three-dimensional projection method and DEM simulations. The analysis identifies critical rock blocks near the bridge, underscoring the need for targeted mitigation strategies. This case study demonstrates the effectiveness of integrating UAV-derived data with DEM for assessing overhanging slope failures and managing rockfall risks in similar geological settings.

Effect of acetylated distarch adipate on fermentation properties of freeze-thawed post-fermented frozen dough and bread characteristics - Man Wang; Xueting Chen; Zuoqian Yang; Miao Wang; Shan Shang; Baoshang Fu; Chengrong Wen (Journal of Cereal Science, 2025)

Induced electric field as alternative pasteurization to improve microbiological safety and quality of bayberry juice - Liping Xue; Zitao Zheng; Yuhang Wu; Lingtao Zhang; Huang Zhang; Na Yang; Xueming Xu; Yamei Jin; Man Meng; Fu Wang (Food Chemistry, 2025)

Calibration of the Solar X-ray Detector on-board the Macao Science Satellite-1B for Soft X-ray Detection - Man-Hei Ng; Xiaoping Zhang; Jianwu Chen; Yongqiang Shi; Fuchang Zuo; Wenxi Peng; Weichun Fu; Liansheng Li; Pengwei Luo; Chi-Long Tang; Guozheng Zhang; Zhiwu Mei; et al. (Science China Earth Sciences, 2025)

Based on TLR4-NLRP3-IL-1β inflammatory pathway: Comparison of necrotizing enterocolitis induced by different classes of antibiotic-induced Cronobacter sakazakii - Danliangmin Song; Jingqi Cheng; Kai Dong; Shiyu Liu; Chaoxin Man; Shiqian Fu; Xinyan Yang; Qianyu Zhao; Yujun Jiang (Food Bioscience, 2024)

Environmental exposure to cadmium induces olfactory neurotoxicity in fire ants and the molecular basis - Xiaohui Xiao; Wenzhen Zhao; Yikang Shao; Changyuan Hu; Jinlong Liu; Guoqing Zhang; Fuxiang Yang; Jing Zhao; Yueguan Fu; Lei Li; Man-Qun Wang; Aiming Zhou (Environmental Pollution, 2024)

Efficient chromium remediation using eco-innovative biochar in a novel two-stage upflow fixed bed system - Jingyi Wang; Yongduo Guan; Jiahui Fu; Xiaochen Liu; Mingfeng Guo; Junzhu Gao; Man Yang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Journal of Water Process Engineering, 2024)

Screening of saline-alkali tolerant microorganisms and their promoting effects on rice growth under saline-alkali stress - Jiahui Fu; Yawen Liu; Xiaochen Liu; Mingfeng Guo; Junzhu Gao; Man Yang; Xuesheng Liu; Wei Wang; Yu Jin; Juanjuan Qu (Journal of Cleaner Production, 2024)

Decoding the Preparation Stage of Target Shooting under Audiovisual Restricted Conditions: Investigating Neural Mechanisms Using Microstate Analysis - Huijie Man; Anmin Gong; Xiaoou Song; Yijing Zhang; Yalan Zhou; Yunfa Fu (Brain Topography, 2024)

Low-temperature subcritical water dechlorination composites of waste PVC/coal fly ash with powerful sensing activity for chemiluminescent detection of acetamiprid and imidacloprid - Fu-Rong Xiu; Xue Bai; Yingying Qi; Xiang Gao; Man Zhao (Science of The Total Environment, 2024)

Research advances in detection of food adulteration and application of MALDI-TOF MS: A review - Danliangmin Song; Kai Dong; Shiyu Liu; Shiqian Fu; Feng Zhao; Chaoxin Man; Yujun Jiang; Kuangyu Zhao; Bo Qu; Xinyan Yang (Food Chemistry, 2024)

Adaptive roles of cytokinins in enhancing plant resilience and yield against environmental stressors - Nishbah Mughal; Noman Shoaib; Jianhua Chen; Yang li; Yuhong He; Man Fu; Xingyun Li; Yuanyuan He; Jinya Guo; Juncai Deng; Wenyu Yang; Jiang Liu (Chemosphere, 2024)

Failure Mechanism and Active Support of Large-Span Tunnel with Unstable Rock Blocks: A Case Study - Wen-xu Li; Zhi-chao Xue; Le-min Liu; Shuo Zhang; Fu-yong Zhang; Wei-teng Li; Xin-jie Man; Xing Shao; Ming-fa Wang; Chang-an Zhang (Geotechnical and Geological Engineering, 2024)

Inflammasome functional activities in B lymphocytes - Man Lun Hsu; Kai Fu Jhuang; Moncef Zouali (Immunologic Research, 2024)

Tracing the centennial variation of East Asian Summer Monsoon - Heng Fu; Feng Shi; Wei Liu; Huihong Xue; Wenmin Man; Juan Li; Zhengtang Guo (Global and Planetary Change, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

Recent progresses on emerging biosensing technologies and portable analytical devices for detection of food allergens - Danqing Zhu; Shiqian Fu; Xiru Zhang; Qianyu Zhao; Xinyan Yang; Chaoxin Man; Yujun Jiang; Ling Guo; Xianlong Zhang (Trends in Food Science & Technology, 2024)

Insights into synergetic modulation of nickel sites over graphene by introducing tungsten and light for efficient methanol electrooxidation - He Xiao; Wenxiang Wang; Man Zhao; Zimei Fu; Meng Bai; Li Zhang; Junming Zhang; Ergui Luo; Jian Zhang; Haishun Wu; Jianfeng Jia (Chemical Engineering Journal, 2024)

Advances in understanding the regulation effect of carbon dots on intrinsic activity of metal and metal-free catalysts for electrocatalysis reaction - Meng Bai; Zimei Fu; Chunmei Liu; Peipei Zhao; Jiamin Ma; Wenxiang Wang; He Xiao; Junwei Wu; Man Zhao; Jianfeng Jia (Chemical Engineering Journal, 2024)

Incidence, characteristics, and risk factors of drug-associated muscle adverse reaction: a retrospective real-world study of inpatients - Anqi Zhao; Daihong Guo; Man Zhu; Ao Gao; Peng Li; An Fu (European Journal of Clinical Pharmacology, 2024)

Soil amendments reduce CH4 and CO2 but increase N2O and NH3 emissions in saline-alkali paddy fields - Hu Cui; Hui Zhu; Fu-Man Zhang; Xin-Yi Wang; Sheng-Nan Hou; Wei-Dong Feng (Science of The Total Environment, 2024)

Experimental and modeling study of adsorption behavior of CH3I over microchannel reactors - Qing He; Lei Zhang; Peize Han; Man Fu; Guorui Zhu (Process Safety and Environmental Protection, 2024)

Optimization of alkaline hydrothermal treatment for humic acids production from corn straw digestate using the response surface methodology - Shuai-Ze Han; Bo-Tao Zhang; Man-Qian Wang; Rong-Bo Guo; Shan-Fei Fu (Journal of Environmental Chemical Engineering, 2024)

Self-assembled Fe3O4-NH2 @g-C3N4 composite for magnetic solid-phase extraction of benzophenones in sea water and lake water coupled with LC-MS/MS determination - Man-Man Wang; Zi-Ling Li; Han Wu; Ke-Yan Chen; Fan Guo; Gui-Fu Zuo; Yu He; Xue-Bo Yin (Journal of Hazardous Materials, 2024)

Diverse indole-diterpenoids with protein tyrosine phosphatase 1B inhibitory activities from the marine coral-derived fungus Aspergillus sp. ZF-104 - Fei Zhang; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Qing-Yun Ma; Lu-Ting Dai; Li-Man Zhou; Hao-Fu Dai; Fan-Dong Kong; Du-Qiang Luo; You-Xing Zhao (Phytochemistry, 2023)

Human dental pulp stem cells have comparable abilities to umbilical cord mesenchymal stem/stromal cells in regulating inflammation and ameliorating hepatic fibrosis - Peixing Chen; Yanchun Lin; Wenbo Lin; Yun Li; Ting Fu; Yuanyue Liu; Tian Guan; Man Xin; Ling Ye; Peiluan Wang; Haoyu Zeng; Kaitao Yao (Human Cell, 2023)

Association between prenatal exposure to per- and polyfluoroalkyl substances and neurodevelopment in children: Evidence based on birth cohort - Xin-xin Gao; Qian-lin Zuo; Xi-hang Fu; Ling-ling Song; Man-qiu Cen; Jing Wu (Environmental Research, 2023)

Tuning MXene electrical conductivity towards multifunctionality - Lu Jia; Suqin Zhou; Abbas Ahmed; Zhichao Yang; Shuqiang Liu; Hua Wang; Fu Li; Man Zhang; Yujing Zhang; Luyi Sun (Chemical Engineering Journal, 2023)

Lithiophilic Sn layer via pre-electroplating to realize the uniform stripping/plating for dendrite free Li metal anodes - Wenlong Liu; Jianzong Man; Yiwen Guo; Yehong Du; Kun Liu; Haibang Zhang; Xiaodong Sun; Ning Zhang; Shize Fu; Juncai Sun (Chemical Engineering Journal, 2023)

Efficient genome editing in cotton using the virus-mediated CRISPR/Cas9 and grafting system - Wei-Feng Guo; Dan-Dan Guo; Fen Li; Shen-Zhai Shang; Ting-Wan Li; Ying-Chao Tang; Man Jiang; Fu-Chun Xu; Wei Gao (Plant Cell Reports, 2023)

Using association mapping and local interval haplotype association analysis to improve the cotton drought stress response - Wenju Gao; Qin Chen; Jincheng Fu; Hui Jiang; Fenglei Sun; Shiwei Geng; Yuxiang Wang; Jieyin Zhao; Yuting Xie; Man Zhou; Yanying Qu; Quanjia Chen (Plant Science, 2023)

Profiling of the spatiotemporal distribution, risks, and prioritization of pharmaceuticals and personal care products in coastal waters of the northern Yellow Sea, China - Xiaotong Guo; Min Lv; Lehui Song; Jing Ding; Mingsan Man; Longwen Fu; Shuang Lu; Lijun Hou; Lingxin Chen (Journal of Hazardous Materials, 2023)

Engineering the S-scheme heterojunction between NiO microrods and MgAl-LDH nanoplates for efficient and selective photoreduction of CO2 to CH4 - Hongli Yang; Huilin Hou; Man Yang; Zhongli Zhu; Hui Fu; Dongdong Zhang; Yong Luo; Weiyou Yang (Chemical Engineering Journal, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Countering beta-cypermethrin: partitioning roles of the insect gut and its bacteria - Li Bai; Xiao-Lin Cai; Man-Yu Li; Fu-Xiao Wang; Chuan-Shan Zou; Jun-Sheng Zhang; Ming-Yu Xie; Feng-Hui Qi; Tian-Zhong Jing (Journal of Pest Science, 2023)

Influence of Cathode Modification by Chitosan and Fe3+ on the Electrochemical Performance of Marine Sediment Microbial Fuel Cell - Xuerong Zai; Man Guo; Xiang Huang; Huaijing Zhang; Yan Chen; Hongwei Ji; Yubin Fu (Journal of Ocean University of China, 2023)

RETRACTED: Perfluorinated compound correlation between human serum and drinking water: Is drinking water a significant contributor? - Shengnian Wu; Tingting Yuan; Wei Fu; Huiyu Dong; Ying Zhang; Man Zhang; Caifang Jiang; Qian Xu; Liping Zhang; Zhimin Qiang (Science of The Total Environment, 2023)

The effects of pulsed electric fields treatment on the structure and physicochemical properties of dialdehyde starch - Ying Li; Jin-Hua Wang; Yu Han; Fu-Hao Yue; Xin-An Zeng; Bo-Ru Chen; Man-Qin Zeng; Meng-Wai Woo; Zhong Han (Food Chemistry, 2023)

Ultrafast extraction of uranium from seawater using photosensitized biohybrid system with bioinspired cascaded strategy - Man Wang; Lijuan Feng; Guangsheng Luo; Tiantian Feng; Shilei Zhao; Hui Wang; Se Shi; Tao Liu; Qiongyao Fu; Jingquan Li; Ning Wang; Yihui Yuan (Journal of Hazardous Materials, 2023)

Curbing per- and polyfluoroalkyl substances (PFASs): First investigation in a constructed wetland-microbial fuel cell system - Bin Ji; Yaqian Zhao; Yang Yang; Qiwen Li; Ying Man; Yunv Dai; Jingmiao Fu; Ting Wei; Yiping Tai; Xiaomeng Zhang (Water Research, 2023)

Facilitating both anionic and cationic redox processes in Na-rich layered cathode materials by heteroatomic doping - Ziwei Chen; Maolin Yang; Zhongyuan Huang; Yanda Fu; Zhefeng Chen; Simo Li; Minzhi zhan; Rui Wang; Mihai Chu; Rui Qi; Xing Cheng; Zhewen Ma; et al. (Chemical Engineering Journal, 2023)

Monitoring of tree tilt motion using lorawan-based wireless tree sensing system (IoTT) during super typhoon Mangkhut - Wai Yi Chau; Yu-Hsing Wang; Siu Wai Chiu; Pin Siang Tan; Mei Ling Leung; Hoi Lun Lui; Jimmy Wu; Yun Man Lau; Kuan-Fu Liu; Billy Chi Hang Hau (Agricultural and Forest Meteorology, 2023)

Association between pyrethroid exposure and risk of depressive symptoms in the general US adults - Hui-ru Li; Xi-hang Fu; Ling-ling Song; Man-qiu Cen; Jing Wu (Environmental Science and Pollution Research, 2023)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

Inhibition of Microglial NLRP3 with MCC950 Attenuates Microglial Morphology and NLRP3/Caspase-1/IL-1β Signaling In Stress-induced Mice - Qing Liu; Man-Man Zhang; Min-Xia Guo; Qiu-Ping Zhang; Na-Zhi Li; Jie Cheng; Shi-Le Wang; Guang-Hui Xu; Cheng-Fu Li; Ji-Xiao Zhu; Li-Tao Yi (Journal of Neuroimmune Pharmacology, 2022)

Dissolved oxygen gradient on three dimensionally printed microfluidic platform for studying its effect on fish at three levels: cell, embryo, and larva - Ping Liu; Longwen Fu; Bowei Li; Mingsan Man; Yunxia Ji; Qi Kang; Xiyan Sun; Dazhong Shen; Lingxin Chen (Environmental Science and Pollution Research, 2022)

Use of an Effective Variance Chemical Mass Balance Model for Source Apportionment of Metal Elements in a Polluted River - Pei-Yuan Hsieh; Chi-Chang Ho; Gen-Shuh Wang; Yuan-Cheng Hsu; Di-Wen Wang; Yu-Man Shang; Chang-Fu Wu (Environmental Processes, 2022)

Spatially-explicit quantitative relationship for a potential PES mechanism: Cascade hydropower development in Yarlung Zangbo River Basin, China - Xiao-kang Zhu; Bin Fu; Ramon Felipe Bicudo Da Silva; Ying-man Guo; Chan-yuan Qin; Ting Feng; Hai-bing Yu; Kuang Xiao (Journal of Mountain Science, 2022)

Bibliometric Review of Biodiversity Offsetting During 1992–2019 - Shuling Yu; Baoshan Cui; Chengjie Xie; Ying Man; Jing Fu (Chinese Geographical Science, 2022)

Artificial modification of Earth’s radiation belts by ground-based very-low-frequency (VLF) transmitters - Binbin Ni; Man Hua; Xudong Gu; Song Fu; Zheng Xiang; Xing Cao; Xin Ma (Science China Earth Sciences, 2022)

Genetic diversity and structure of Oncomelania hupensis hupensis in two eco-epidemiological settings as revealed by the mitochondrial COX1 gene sequences - Jie-Ying Zhang; Man-Man Gu; Qiu-Fu Yu; Meng-Tao Sun; Hui-Ying Zou; Zhi-Jun Zhou; Da-Bing Lu (Molecular Biology Reports, 2022)

Three new dimeric 2-(2-phenylethyl)chromones from artificial agarwood of Aquilaria sinensis - Pan Xiang; Wen-Hua Dong; Cai-Hong Cai; Wei Li; Li-Man Zhou; Hao-Fu Dai; Hui-Qin Chen; Wen-Li Mei (Natural Product Research, 2021)

Dynamic process of rock avalanche and dynamic interaction between rock avalanche and hazard-bearing bodies - Zhong Fu Wang; Man He; Yan Wang; Jingzhuo Yang; Haoyuan Li (Arabian Journal of Geosciences, 2021)

3D Step-by-step inversion strategy for audio magnetotellurics data based on unstructured mesh - San Cheng; Zhi-Yong Zhang; Feng Zhou; Man Li; Hui Chen; Fu-Sheng Shi; Lin-Pin Huang; Yong Li (Applied Geophysics, 2021)

3-Aminopropyltriethoxysilane Complexation with Iron Ion Modified Anode in Marine Sediment Microbial Fuel Cells with Enhanced Electrochemical Performance - Xuerong Zai; Man Guo; Yaokang Hao; Shaoxin Hou; Zhiwei Yang; Jia Li; Yang Li; Hongwei Ji; Yubin Fu (Journal of Ocean University of China, 2021)

Effects of Cedrus atlantica extract on acute myeloid leukemia cell cycle distribution and apoptosis - Pei-Hsiu Hung; Ming-Chang Hsieh; Shan-Chih Lee; Xiao-Fan Huang; Kai-Fu Chang; Szu-Yin Chen; Ming-Shih Lee; Nu-Man Tsai (Molecular Biology Reports, 2020)

SNX-2112, an Hsp90 inhibitor, suppresses cervical cancer cells proliferation, migration, and invasion by inhibiting the Akt/mTOR signaling pathway - Liang-Shun Fu; Hong-Hong Qiu; Min Liu; Liu-Bing Hu; Yan Wang; Peng-Chao Zhang; Man-Mei Li; Yi-Fei Wang; Zhong Liu (Medicinal Chemistry Research, 2020)

Enhanced pyrogallol toxicity to cyanobacterium Microcystis aeruginosa with increasing alkalinity - Yunni Gao; Qinqin Fu; Jing Lu; Hui Yang; Philip T. Orr; Fang Zhang; Jing Dong; Man Zhang; Qianhong Gu; Chuanjiang Zhou; Michele A. Burford (Journal of Applied Phycology, 2020)

Preparation, Characteristics, and Formation Mechanism of Oyster Peptide-Zinc Nanoparticles - Hai Huang; Man Fu; Meihua Chen (Journal of Ocean University of China, 2019)

Changes of non-protein thiols in root and organic acids in xylem sap involved in cadmium translocation of cadmium-safe rice line (Oryza Sative L.) - Qin Li; Jingyi Guo; Xizhou Zhang; Haiying Yu; Fu Huang; Lu Zhang; Man Zhang; Tingxuan Li (Plant and Soil, 2019)

Colonization cues of leaf- and root-inhabiting bacterial microbiota of Atractylodes lancea derived in vitro and in vivo - Yong Jia; WanQiu Fu; Man Xu; JiaYu Zhou; RiSheng Xu; ChuanChao Dai (Plant and Soil, 2018)

mPGES-1-derived prostaglandin E2 stimulates Stat3 to promote podocyte apoptosis - Jing Yu; Yimei Wu; Lu Wang; Wen Zhang; Man Xu; Jiayu Song; Yu Fu; Yiyun Cui; Wei Gong; Shuzhen Li; Weiwei Xia; Songming Huang; et al. (Apoptosis, 2017)

Landscape dynamics and driving forces of wetlands in the Tumen River Basin of China over the past 50 years - Xiao Jun Zheng; Peng Sun; Wei Hong Zhu; Zhen Xu; Jing Fu; Wei Dong Man; Hai Long Li; Jian Zhang; Lei Qin (Landscape and Ecological Engineering, 2017)

Neuroprotection of Sevoflurane Against Ischemia/Reperfusion-Induced Brain Injury Through Inhibiting JNK3/Caspase-3 by Enhancing Akt Signaling Pathway - Xiang-Ru Wen; Yan-Yan Fu; Hong-Zhi Liu; Jian Wu; Xiao-Ping Shao; Xun-Bao Zhang; Man Tang; Yue Shi; Kai Ma; Fang Zhang; Yi-Wen Wang; Hui Tang; et al. (Molecular Neurobiology, 2016)

Hydrotubation Combined with Chinese Herbal Medicine for Salpingitic Infecundity: A Systematic Review and Meta-Analysis - Huanhuan Wen; Jinrong Fu; Hong Tang; Man Ge; Linna Feng (Cell Biochemistry and Biophysics, 2015)

Quinoxaline-2,3-diones: potential d-amino acid oxidase (DAAO) inhibitors - Dongsheng Xie; Yanchao Wang; Jin Xie; Jun Lu; Junjun Cui; Man Zhang; Lei Fu; Yongxiang Wang (Medicinal Chemistry Research, 2014)

Bird species migration ratio in East Asia, Australia, and surrounding islands - Yiliang Kuo; Da-Li Lin; Fu-Man Chuang; Pei-Fen Lee; Tzung-Su Ding (The Science of Nature, 2013)

The diversity of soil culturable fungi in the three alpine shrub grasslands of Eastern Qilian Mountains - Junzhong Zhang; Baiying Man; Benzhong Fu; Li Liu; Changzhi Han (Frontiers of Earth Science, 2013)

The unsulfated extracellular N-terminus of vGPCR reduces the tumorigenicity of hGRO-α in nude mice - Hui Wu; YongMing Fu; Jun Xiao; Man Zhou; Wei Zhou; Hao Feng (Science China Life Sciences, 2013)

Tissue concentrations, bioaccumulation, and biomagnification of synthetic musks in freshwater fish from Taihu Lake, China - Xiaolan Zhang; Qing Xu; Shoukuan Man; Xiangying Zeng; Yingxin Yu; Yuping Pang; Guoying Sheng; Jiamo Fu (Environmental Science and Pollution Research, 2013)

Al-induced secretion of organic acid, gene expression and root elongation in soybean roots - Daoming Wu; Man Zhao; Shouying Shen; Youqiang Fu; Takayuki Sasaki; Yoko Yamamoto; Wenhui Wei; Hong Shen (Acta Physiologiae Plantarum, 2013)

Efficacy of endosulfan and fipronil and joint toxic action of endosulfan mixtures against Leptinotarsa decemlineata (Say) - Xiao-qin Shi; Man-Hui Xiong; Wei-Hua Jiang; Zhi-Tian Wang; Wen-Chao Guo; Zhen-Han Xia; Wen-Jun Fu; Guo-Qing Li (Journal of Pest Science, 2012)

A review of the anticancer and immunomodulatory effects of Lycium barbarum fruit - Wai-Man Tang; Enoch Chan; Ching-Yee Kwok; Yee-Ki Lee; Jian-Hong Wu; Chun-Wai Wan; Robbie Yat-Kan Chan; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2012)

Quantitative assessment of the associations between four polymorphisms (FokI, ApaI, BsmI, TaqI) of vitamin D receptor gene and risk of diabetes mellitus - Qijuan Wang; Bo Xi; Kathleen Heather Reilly; Man Liu; Maosun Fu (Molecular Biology Reports, 2012)

Apoptosis induced by 1,3,6,7-tetrahydroxyxanthone in Hepatocellular carcinoma and proteomic analysis - Wei-ming Fu; Jin-fang Zhang; Hua Wang; Hong-sheng Tan; Wei-mao Wang; Shih-Chi Chen; Xiao Zhu; Tak-ming Chan; Ching-man Tse; Kwong-sak Leung; Gang Lu; Hong-xi Xu; et al. (Apoptosis, 2012)

A Comparison Study Between Spring and Summer Fogs in the Yellow Sea-Observations and Mechanisms - Suping Zhang; Man Li; Xiangui Meng; Gang Fu; Zhaopeng Ren; Shanhong Gao (Pure and Applied Geophysics, 2012)

Inhibitory Effect of Delphinidin on Monocyte–Endothelial Cell Adhesion Induced by Oxidized Low-Density Lipoprotein via ROS/p38MAPK/NF-κB Pathway - Chun-ye Chen; Long Yi; Xin Jin; Ting Zhang; Yu-jie Fu; Jun-dong Zhu; Man-tian Mi; Qian-yong Zhang; Wen-hua Ling; Bin Yu (Cell Biochemistry and Biophysics, 2011)

cDNA cloning and characterization of UDP-glucose: anthocyanidin 3-O-glucosyltransferase in Freesia hybrida - Xin Sui; Xiang Gao; Man Ao; Qinmei Wang; Dan Yang; Meng Wang; Yang Fu; Li Wang (Plant Cell Reports, 2011)

Molecular Identification and Physiological Characterization of a Putative Novel Plasma Membrane Protein from Arabidopsis Involved in Glucose Response - Moon-Soo Chung; Ping Huang; Chan Man Ha; Ji Hyung Jun; Sung-Ju Ahn; Fu-chun Zhang; Hyun-Jong Bae; Baik Ho Cho; Cheol Soo Kim (Journal of Plant Biology, 2011)

Molecular Cloning and Expression of IL2 cDNA from the Tibet Pig - Li Hui; Gao Rong; Wu Mei; Wang Li-Huan; Fu Man-Liang; Wu Kai-Yuan (Veterinary Research Communications, 2005)

Two genes encoding protein phosphatase 2A catalytic subunits are differentially expressed in rice - Richard Man Kit Yu; Yan Zhou; Zeng-Fu Xu; Mee-Len Chye; Richard Yuen Chong Kong (Plant Molecular Biology, 2003)